Identification of moth and butterfly diversity (Lepidoptera) in the Universitas Tidar area - Ihwani, Afidatul; Prajoko, Setiyo; Permadani, Karunia Galih (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2025)
Lepidoptera (butterflies and moths) diversity is a crucial indicator of an ecosystem’s environmental condition. However, the development of residential areas and the conversion of green land to other uses have led to declines in population and the diversity of these species. One potential area for research is the Universitas Tidar area, as there has been little research on Lepidoptera in this region. This study aims to determine the composition of Lepidoptera species, analyse diversity, uniformity, and dominance indices, and examine abiotic factors that support Lepidoptera diversity in the area. This study employed the Visual Encounter Survey (VES) method, combined with Time Search observation plots, and analysed the data using the Shannon-Wiener diversity index, Evenness uniformity, and Simpson’s dominance. Based on the study’s results, 28 species comprising 186 individuals were identified across two suborders: Rhopalocera, including Nymphalidae, Pieridae, Papilionidae, Lycaenidae, and Hesperiidae, and Heterocera, including Erebidae, Crambidae, and Zygaenidae. The diversity index value (H’) of Tuguran Campus is 2.27. Sidotopo has a uniformity index value (E) of 2.67 (medium), while the uniformity index value (E) at Tuguran Campus is 0.84. Sidotopo has a uniformity index value (E) of 0.86 (high), indicating that both locations have a balanced community. The domination index value (C) of Tuguran Campus is 0.16, and Sidotopo has a domination index value (C) of 0.09 (low). Abiotic factors that affect the presence and diversity of Lepidoptera in a habitat include light intensity, humidity, temperature, and wind speed.